2013
DOI: 10.1073/pnas.1210353110
|View full text |Cite
|
Sign up to set email alerts
|

Met synergizes with p53 loss to induce mammary tumors that possess features of claudin-low breast cancer

Abstract: Triple-negative breast cancer (TNBC) accounts for ∼20% of cases and contributes to basal and claudin-low molecular subclasses of the disease. TNBCs have poor prognosis, display frequent mutations in tumor suppressor gene p53 (TP53), and lack targeted therapies. The MET receptor tyrosine kinase is elevated in TNBC and transgenic Met models (Met mt ) develop basal-like tumors. To investigate collaborating events in the genesis of TNBC, we generated Met mt mice with conditional loss of murine p53 (Trp53) in mamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
64
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(72 citation statements)
references
References 54 publications
7
64
0
1
Order By: Relevance
“…We have found that Sp1 can also activate the miR-200cϳ141 promoter; however this effect may be indirect as binding of endogenous Sp1 has not been detected in its promoter region. Interestingly, in breast cancer, p53 reduction or mutation can augment loss of miR-200 levels, but penetrance is often incomplete and is dependent on activation of other signaling pathways (such as HGF signaling via MET) for a full EMT (60,61). This would be in keeping with the notion that activation of mesenchymal signaling pathways are needed to sustain repression of miR-200.…”
Section: Discussionsupporting
confidence: 63%
“…We have found that Sp1 can also activate the miR-200cϳ141 promoter; however this effect may be indirect as binding of endogenous Sp1 has not been detected in its promoter region. Interestingly, in breast cancer, p53 reduction or mutation can augment loss of miR-200 levels, but penetrance is often incomplete and is dependent on activation of other signaling pathways (such as HGF signaling via MET) for a full EMT (60,61). This would be in keeping with the notion that activation of mesenchymal signaling pathways are needed to sustain repression of miR-200.…”
Section: Discussionsupporting
confidence: 63%
“…Upregulation of mesenchymal biomarkers and Met activation have both been associated separately with prognosis in several tumor types (6,(31)(32)(33) and coexistence of both markers with stemness (34). One could hypothesize that the presence of a subset of cells with these markers in SCLC at diagnosis could predict the enrichment of this chemoresistant population at progression after chemotherapy and, therefore, explain the poor prognosis of these patients in our study.…”
Section: Discussionmentioning
confidence: 62%
“…9 In HCC827 GR2 cells, AXL kinase expression was too low for detection by western blotting, and although HCC4006 GR3 cells clearly expressed AXL, they did not require the kinase for survival. In addition, while some reports show that aberrant Met activation via mutation or ligand activity secreted by stromal cells induces EMT and promotes invasion of carcinoma cells in many types of cancers, [35][36][37] the GR cells characterized in this study did not depend on Met signaling for survival. This is in line with previous work by others showing that EGFR TKI-resistant EGFR-mutant cells with an EMT phenotype were uniformly not dependent on Met kinase.…”
Section: Discussionmentioning
confidence: 83%